Assessing multidecadal runoff (1970–2010) using regional hydrological modelling under data and water scarcity conditions in Peruvian Pacific catchment - Rau, P. (2019)
In a context of water scarcity in Peruvian Pacific catchments as a crucial issue for Peru, added to the paucity of data availability, we propose a methodology that provides new perspectives for freshwater availability estimation as a base reference for unimpaired conditions. Under those considerations, a regional discharge of 709 m3/s to the Pacific Ocean is estimated with a significant increasing trend of about 43 m3/s per decade over the 1970–2010 period. To represent the multidecadal behaviour of freshwater runoff along the region, a regional runoff analysis is proposed based on hydrological modelling at annual and monthly time step for unimpaired conditions over the whole 1970–2010 period. Differential Split-Sample Tests are used to assess the hydrological modelling robustness of the GR1A and GR2M conceptual lumped models, showing a satisfactory transposability from dry to wet years inside the thresholds defined for Nash–Sutcliffe and bias criteria. This allowed relating physical catchment characteristics with calibrated and validated model parameters, thus offering a regional perspective for dryland conditions in the study area (e.g., the anticlockwise hysteresis relationship found for seasonal precipitation–runoff relationship) as well as the impacts of climate variability and catchment characteristics.